Characteristics, Needs, and Perspectives of Individuals Living Alone With Dementia: An Integrative Review - Sara J. Crance; Fang Yu (Health Science Reports)
ABSTRACT Background The number of individuals living alone with dementia is increasing throughout the world, and they have unique needs that are poorly understood. The aim of this integrative review was to understand the characteristics, needs, and perspectives of individuals living alone with dementia as well as the available community resources to guide future research and clinical practice. Methods Electronic (PubMed, CINAHL, and PsycINFO) and manual searches were utilized to identify articles using MeSH terms. Among 5693 identified articles, 31 articles met the eligibility criteria. The quality of the articles was determined utilizing the Joanna Briggs Institute (JBI) Critical Appraisal Tools applicable to the study design. Results Individuals living alone with dementia are more likely to be widows, of older age, and lower income, have a higher risk of severe loneliness despite more social contact, higher functional ability, and higher unmet needs despite the use of services, compared to those living with others. Perspectives of individuals living alone with dementia focus on the uncertainty of diagnosis, cognitive fluctuations, and maintaining independence. Lack of specialized services available after diagnosis and barriers to accessing services may lead to decreased independence and increased uncertainty. Overall, there is a lack of specialized services, person‐centered care, and support to meet their unique needs. Conclusion Individuals living alone with dementia have unique characteristics, unmet needs, and use of available services, which should be assessed regularly. Future research is needed to develop community‐based, person‐centered services for them and remove barriers to service use.